2020
DOI: 10.3390/pathogens9090747
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Drug Targets in Helicobacter pylori Using In Silico Subtractive Proteomics Approaches and Their Possible Inhibition through Drug Repurposing

Abstract: The class 1 carcinogen, Helicobacter pylori, is one of the World Health Organization’s high priority pathogens for antimicrobial development. We used three subtractive proteomics approaches using protein pools retrieved from: chokepoint reactions in the BIOCYC database, the Kyoto Encyclopedia of Genes and Genomes, and the database of essential genes (DEG), to find putative drug targets and their inhibition by drug repurposing. The subtractive channels included non-homology to human proteome, essentiality analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 83 publications
3
13
0
Order By: Relevance
“…To the best of our knowledge, this is the first time that OGEE was used to retrieve essential proteins. Most previous similar studies have used databases such as the Database of Essential Genes (DEG) and Geptop instead [ 12 , 13 , 15 , 17 ]. Avoiding possible undesired effects in human hosts is important, so essential proteins that are non-homologous to the human proteome were identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first time that OGEE was used to retrieve essential proteins. Most previous similar studies have used databases such as the Database of Essential Genes (DEG) and Geptop instead [ 12 , 13 , 15 , 17 ]. Avoiding possible undesired effects in human hosts is important, so essential proteins that are non-homologous to the human proteome were identified.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial activity of these organic acids has been previously reported in several studies [ 67 , 68 , 69 ]. It has been reported that citric acid exhibits antibacterial activity against Helicobacter pylori and Pseudomonas aeruginosa [ 12 , 68 , 70 ]. Over et al reported the antibacterial activity of some organic acids, including both citric acid and tartaric acid on Escherichia coli O157:H7, Listeria monocytogenes and Salmonella typhimurium [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of the genomic sequences of pathogenic bacteria has provided huge data that can be used for identifying potential drug and vaccine targets through subtractive genomic, proteomic or transcriptomic approaches (Nandode et al, 2012;Yan and Gao, 2020). Using a subtractive proteomic approach, we previously identified 17 essential targets in H. pylori with 42 possible Drugbank ligands, of which several small organic acids were potential ligands for many of the retrieved essential targets (Ibrahim et al, 2020). These molecules have a well-known antibacterial activity, such as (S)-3-phenyllactic acid (Mu et al, 2012), citric acid (Adamczak et al, 2020), malonic acid (Feng et al, 2010), dipicolinic acid (Jadamus et al, 2005), and D-tartaric acid (Hu et al, 2019;Coban, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…ADC was identified as a Mycobacterium tuberculosis drug target inhibited by pyrazinamide (Gopal et al, 2020). Malonic acid was proposed as a potential inhibitor of the H. pylori ADC enzyme (Ibrahim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%